Excellent reliability of the Hamilton Depression Rating Scale (HDRS‐21) in Indonesia after training. (19th July 2013) - Istriana, Erita; Kurnia, Ade; Weijers, Annelies; Hidayat, Teddy; Pinxten, Lucas; de, Cor; Schellekens, Arnt
Abstract Introduction The Hamilton Depression Rating Scale (HDRS) is the most widely used depression rating scale worldwide. Reliability of HDRS has been reported mainly from Western countries. The current study tested the reliability of HDRS ratings among psychiatric residents in Indonesia, before and after HDRS training. The hypotheses were that: (i) prior to the training reliability of HDRS ratings is poor; and (ii) HDRS training can improve reliability of HDRS ratings to excellent levels. Furthermore, we explored cultural validity at item level. Methods Videotaped HDRS interviews were rated by 30 psychiatric residents before and after 1 day of HDRS training. Based on a gold standard rating, percentage correct ratings and deviation from the standard were calculated. Results Correct ratings increased from 83% to 99% at item level and from 70% to 100% for the total rating. The average deviation from the gold standard rating improved from 0.07 to 0.02 at item level and from 2.97 to 0.46 for the total rating. Discussion HDRS assessment by psychiatric trainees in Indonesia without prior training is unreliable. A short, evidence‐based HDRS training improves reliability to near perfect levels. The outlined training program could serve as a template for HDRS trainings. HDRS items that may be less valid for assessment of depression severity in Indonesia are discussed.